MODEL PEMBELAJARAN COOPERATIF INTEGRATED READING AND COMPOSITION MENINGKATKAN HASIL BELAJAR PPKn MAN 1 PONTIANAK - Rahmania, Siti; Sulistyarini, Sulistyarini; Bistari, Bistari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was aimed to improve the students’ learning outcomes by using the Cooperative Integrated Reading and Composition (CIRC) learning model on the material subject of A Threat to the State in the Frame of Bhinneka Tunggal Ika. This is a Classroom Action Research (CAR) on the class X IA I students of MAN 1 Pontianak, of which thirty-two students took part as the sample of this study. The data were collected using test and observation techniques. The data analysis was done using a statistic descriptive analysis technique. The findings showed that the implementation of the CIRC model in cycle 1 was categorized good, with a total score of 49, percentage by 76.5%, and cycle 2 was categorized very good, with a total score of 55, percentage by 85%. The learning outcomes by using the selected learning model increased by 8.5%. The percentage of completeness in students’ learning outcomes was 44% in cycle 1, with the average score by 70, and 85% in cycle 2, with the average score by 77.5. Therefore, implementing the CIRC learning model in the Civic Education subject can improve the learning outcomes of the class X IA I students of MAN 1 Pontianak. Keywords: Effectiveness, Listening Team, Learning Outcomes, Civic Education